Pengaruh Dosis Pupuk Pada Pertumbuhan dan Hasil Varietas Kubis (Brassica Oleracea L.) Sehati di Sekitar Lahan Agroforestri - Ramat Joko Nugroho; Johar Latifah Mustikasari; Rennanti Lunaahdliah (Jurnal Riset Rumpun Ilmu Tanaman, 2022)
In recent years, Indonesia's export value which is quite high is the horticulture sector. According to data from the Central Statistics Agency, several types of vegetables have increased every year. One of them is cabbage. However, the high demand for cabbage both domestically and abroad is not compatible with high productivity. One of the efforts that can be done to increase productivity is not only growing cabbage in the highlands. Recently, many new varieties have been found that can be planted in lowland areas with the right dose of fertilizer and treatment. This study aims to determine the effect of fertilizer dose on the growth and yield of the Sehati variety, which is a lowland variety. The research was conducted on land owned by farmers in Kebumen Regency. The research was carried out using RAK with one factor, namely the dose of fertilizer. The results of the observational data obtained were analyzed by analysis of variance (ANOVA) and then further tested with the LSD method at = 5% to determine the difference between the treatments tested. The results showed that P1 (Treatment 1) with a dose of fertilizer (50 kg/ha Urea, 75 kg/ha SP36, 50 kg/ha ZA, 75 kg/ha KCL) had better adaptation in the Surotrunan area. Key words : Brassica Oleracea L., lowland cabbage, fertilizer dose 75 kg/ha SP36, 50 kg/ha ZA, 75 kg/ha KCL) have better adaptations in the Surotrunan area. Key words : Brassica Oleracea L., lowland cabbage, fertilizer dose 75 kg/ha SP36, 50 kg/ha ZA, 75 kg/ha KCL) have better adaptations around teak agroforestry.lands